COVID-19 and the Future of Labour Research, Policy and Regulation. (2nd January 2022) - Stewart, Andrew
ABSTRACT: This article reflects on the profound impact of COVID-19 on labour research and those who undertake it, on both global and local labour markets, and on labour policy and regulation in Australia. It briefly discusses the many existing challenges the pandemic has highlighted for the supply, organisation and compensation of labour in one particular sector, aged care, before going on to examine the state of the Australian system of labour regulation and policy-making prior to the current crisis. It then discusses how that system has responded to the pandemic, and critically analyses the Morrison Government's embrace and then abandonment of the idea of consultation and cooperation with the union movement, as it seeks to set an agenda for Australia's recovery. There seems little chance that the government's package of changes to the Fair Work Act 2009 will do anything to address deep-seated problems such as wage stagnation, insecurity, inequality and adversarialism. Indeed it may exacerbate them.